2003
DOI: 10.1590/s0100-204x2003000800002
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento inicial do cafeeiro Rubi em resposta a doses de nitrogênio, fósforo e potássio e a regimes hídricos

Abstract: Resumo -O objetivo deste trabalho foi avaliar o crescimento da parte aérea do cafeeiro (Coffea arabica L.) cultivar Rubi MG 1192 submetido a três doses de N, P e K e dois regimes hídricos durante o primeiro ano após o transplante, em 20 de novembro de 2000. O crescimento da planta foi avaliado aos 134, 196, 236, 284, 334 e 383 dias após o transplante (DAT). Houve resposta ao N e ao K no crescimento em número de ramos plagiotrópicos por planta, ao passo que no número de nós com gemas por planta, observou-se re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 6 publications
2
15
0
12
Order By: Relevance
“…This is in contrast to the States of Espírito Santo and Rio de Janeiro (Partelli et al, 2010) because the average minimum air temperature, even during the winter period, always remained above 17ºC in the present study ( Figure 1A). It has been demonstrated that C. canephora plants growing at latitudes higher than 15ºS show higher vegetative growth rates during periods with longer, hotter days and higher rainfall, while low vegetative growth rates are observed during periods with colder and shorter days (Nazareno et al, 2003;Partelli et al, 2010). Coffea canephora plants can endure higher temperatures than C. arabica ; however, they are less adapted to low temperatures (DaMatta & Ramalho, 2006;Batista-Santos et al, 2011;Ramalho et al, 2014;Scotti-Campos et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to the States of Espírito Santo and Rio de Janeiro (Partelli et al, 2010) because the average minimum air temperature, even during the winter period, always remained above 17ºC in the present study ( Figure 1A). It has been demonstrated that C. canephora plants growing at latitudes higher than 15ºS show higher vegetative growth rates during periods with longer, hotter days and higher rainfall, while low vegetative growth rates are observed during periods with colder and shorter days (Nazareno et al, 2003;Partelli et al, 2010). Coffea canephora plants can endure higher temperatures than C. arabica ; however, they are less adapted to low temperatures (DaMatta & Ramalho, 2006;Batista-Santos et al, 2011;Ramalho et al, 2014;Scotti-Campos et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the farming of Conilon coffee has been conducted predominantly under irrigation because this condition enhances the production of flower buds (Carvalho, Colombo, Scalco, & Morais, 2006), increases the number of plagiotropic branches per plant (Nazareno et al, 2003), enhances the number of flowers per plant (Massarirambi, Chingwara, & Shongwe, 2009) and results in better development and grain formation (Pezzopane, Castro, Pezzopane, Bonomo, & Saraiva, 2010). Therefore, irrigation guarantees high productivity (Bonomo et al, 2013;Sakai et al, 2015) and a final product with a better beverage quality (Fernandes, Partelli, Bonomo, & Golynski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of water on the increase in TOC and the different fractions may be due to the higher amount of organic material promoted by irrigation in dry periods in the Cerrado. As stated by Nazareno et al (2003), irrigation in this region increases the biomass production of coffee, leading to a greater OC input into the soil.…”
Section: Oxidizible Organic Carbon Fractionsmentioning
confidence: 86%
“…The P content in these soils is generally well below the critical level, around 8 mg dm -3 , for clay soils (Sousa & Lobato, 2004;Reis et al, 2011). This limits crop growth, requiring the application of corrective fertilizer, in view of the high P demand of coffee for fruit production and the rapid initial growth (Nazareno et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Essa suposição pode ser descartada, uma vez que os teores de Si nas raízes foram semelhantes entre os tratamentos controle e com 6 Mg ha -1 de silicato de cálcio (Figura 1). Corroborando esse raciocínio, Sonobe et al (2011) (Nazareno et al, 2003;Silva et al, 2004 O desbalanço na partição de matéria seca entre a parte aérea e as raízes em condições de boa disponibilidade de recursos não trouxe consequências para o crescimento geral da planta, dado pelo acúmulo de matéria seca total (Figura 2g). O contrário pode ocorrer em ambientes com variação significativa da disponibilidade de água, nos quais uma copa bem desenvolvida demandaria maior quantidade de água para suportar a evapotranspiração da cultura.…”
Section: Discussionunclassified